Una aproximación hacia la seguridad hídrica en los Andes tropicales: desafíos y perspectivas - Drenkhan, Fabian (2023)
The tropical Andes represent a key region in terms of biodiversity, cultural diversity, and multiple ecosystem services. They serve as the foundation for human subsistence for millions of inhabitants, which is increasingly affected by growing water insecurity due to the coupled impacts of land cover and climate changes. In recent years, important efforts focused on headwaters in highland areas, implementing payments for environmental services and natural infrastructure, have created several opportunities to address water insecurity in the tropical Andes. However, there is insufficient knowledge to assess levels of water security at spatio-temporal scales suitable for developing locally relevant adaptation strategies. This limitation is due to a scarcity of data combined with inconsistent concepts and metrics, and incomplete approaches to integrate all components of water security within a common framework. In addition, there is a need to align public policies that fit local needs. This study explores current limitations and prospects for studying and increasing water security in the region. The establishment of monitoring and data collection networks, including participatory and diverse knowledge designs, is crucial. Modeling water security modeling requires creating strong linkages between the different components of the water cycle and water users. These efforts should be integrated into a transdisciplinary collaborative framework involving science, policy, and community, faciliting effective, robust, and locally tailored adaptation pathways.